The Rab3 family proteins in age-related neurodegeneration: unraveling molecular pathways and potential therapeutic targets - He, Haijun; Ai, Ruixue; Fang, Evandro Fei; Palikaras, Konstantinos (NPJ Aging, 2025)
The Rab3 protein family is composed of a series of small GTP-binding proteins, including Rab3a, Rab3b, Rab3c, and Rab3d, termed Rab3s. They play crucial roles in health, including in brain function, such as through the regulation of synaptic transmission and neuronal activities. In the high-energy-demanding and high-traffic neurons, the Rab3s regulate essential cellular processes, including trafficking of synaptic vesicles and lysosomal positioning, which are pivotal for the maintenance of synaptic integrity and neuronal physiology. Emerging findings suggest that alterations in Rab3s expression are associated with age-related neurodegenerative pathologies, including Alzheimer's disease, Parkinson's disease, and Huntington's disease, among others. Here, we provide an overview of how Rab3s dysregulation disrupts neuronal homeostasis, contributing to impaired autophagy, synaptic dysfunction, and eventually leading to neuronal death. We highlight emerging questions on how Rab3s safeguards the brain and how their dysfunction contributes to the different neurodegenerative diseases. We propose fine-tuning the Rab3s signaling directly or indirectly, such as via targeting their upstream protein AMPK, holding therapeutic potential.